Formas e sabores: frutas e legumes - Colosso, Cristiane Otília; Lima , Eliene Xavier de; Carmo , Joelma Júlia do; Domingos , Maria Aparecida; Okazaki , Maria Silvia Guimarães (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf